Qualities Considered by Shari'ah for Role Model Personality: Fundamental Analytical Study - Kattoua, Muhammad Turkey (Journal of Islamic and Religious Studies, 2022)
Islamic Sharia is very interested in setting role model personalities. That is because humans naturally tend to be influenced by role models' words and behavior, and great public interests rely on such people. Since a lot of people, recently, have claimed this title for themselves, aided by the information and communication technology revolution, and in order for common people not to confuse those people with real examples, Sharia has set conditions stating special qualities for a person to be a role model, and consequently, for people to see those qualities in their actions and manners. For a role model, from the Islamic viewpoint, must be reasonable, disciplinary, well-mannered and well-educated in Sharia, having several qualities such as dignity and virtuousness, otherwise, the public would be deluded by examples who lack those qualities. So, a Muslim should be careful in choosing his example in life.